Experimental evaluation of a 1.x-effect ejector-absorption refrigeration system. (5th July 2019) - Yan, Xiaona; Shi, Yuqi; Wang, Lin; Hong, Daliang; Chen, Guangming
Highlights: 1.X-effect ejection-absorption experimental rig was experimental studied. The system's external parameters were experimentally studied. A 30.0% higher COP than single-effect cycle. High generation temperature 20 °C lower than double effect system. Abstract: In this paper, a 1.x-effect (hybrid ejector-absorption refrigeration working between single-effect and double-effect) cycle is evaluated experimentally. Through the use of the ejector, the external heat sources' grade is reduced. Part of the refrigerant vapor at the outlet of the low-pressure generator is directly entrained by the refrigerant vapor from the outlet of the high-pressure generator to the condenser. The system with 10 kW cooling load is experimentally studied. The COP of the system is 30.0% higher than a single-effect absorption refrigeration system, and generation temperature is at least 20 °C lower than a double-effect absorption refrigeration system.